Isolation of Outer Membranes with an Ordered Array of Surface Subunits from Acinetobacter - Thornley, Margaret J. (1973)
A method has been developed for the isolation of outer membranes from Acinetobacter sp. strain MJT/F5/199A. Washed cells were broken in a French press and, after deoxyribonuclease and ribonuclease treatment, removal of intact cells, and four washes in 20 mosmol phosphate buffer, pH 7.4, with centrifugation at 25,000 × g for 10 min, preparations of cell wall fragments from which almost all pieces of plasma membrane had been removed resulted. Treatment of the cell walls with lysozyme and further washing, in the presence of 20 mM MgCl(2), yielded preparations of outer membranes. Electron microscopy of freeze-etched preparations shows that a regular pattern of subunits is present on the outer surfaces of intact cells. After negative staining, these subunits are visible on isolated walls and outer membranes; they can be removed by brief treatment with papain. In section, the cell wall structure is that typical of gram-negative bacteria, but the subunits are not detectable on the surface of the outer membrane. The outer membrane retains the appearance of a “unit membrane” in the cell wall, isolated outer membrane, and papain-treated outer membrane fractions. Both cell walls and outer membranes contain a high percentage of protein (76 and 84%, respectively) and not more than 5% carbohydrate, of which glucose and galactose are constitutents. The outer membranes of this Acinetobacter thus differ in structure and composition from those of bacteria in the Enterobacteriaceae.